Study of Escherichia coli antimicrobial resistance in lower urinary tract infections in women - سوزان سمرة; حسان ناصر; رهام ناصر (Latakia University Journal -Medical Sciences Series, 2023)
Urinary tract infection (UTI) is one of the most frequent bacterial infections among females. This study was designed to determine the prevalence of Escherichia coli, as causing agent for UTIs, in women, and to assess the susceptibility of clinically prescribed antibiotics, in treating UTIs. For this purpose, urine samples from 240 non-pregnant outpatient women were collected, at Tishreen University Hospital, in Lattakia, Syria, between 1/1/2020 and 10/30/2020. All patients had symptoms of lower urinary infection, but no urinary tract abnormalities, or obstructive urinary problems (urinary stones or catheters(. The study results showed that 53.84% of UTIs were caused by Escherichia coli, and the most effective antibiotics against the isolated strains were carbapenems (ertapenem, imipenem), piperacillin + tazobactam with an effectiveness of up to 100%, followed by meropenem, colistin, amikacin, with an efficiency that exceeded 90% (96%, 95%, 90%, respectively), then nitrofurantoin, amoxicillin with clavulanic acid (84%, 80%, respectively). Whereas the resistance percentages of the isolated Escherichia coli against ciprofloxacin, levofloxacin, and cefixime were 35.3%, 36.4%, and 56.23%, respectively). Our results concluded the importance of conducting antibiotic susceptibility tests before prescribing antibiotics for UTIs-treatment.